4se the following function rule to find \( f(2) \) \( f(x)=9(8)^{x}+10 \) \( f(2)=\square \)
Solución de inteligencia artificial de Upstudy
Responder
Solución

¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.

Respondido por UpStudy AI y revisado por un tutor profesional
Extra Insights
To find \( f(2) \), substitute \( 2 \) into the function rule: \( f(2) = 9(8)^{2} + 10 \). Calculating \( (8)^{2} \) gives \( 64 \), so the expression becomes: \( f(2) = 9(64) + 10 = 576 + 10 = 586 \). Thus, \( f(2) = 586 \). Remember, when substituting values into functions, always follow the order of operations. That means doing any exponents first, followed by multiplication, and finally addition. It's a nifty way to keep all your calculations tidy and accurate!
